A Comparative Phytochemical Analysis of Abhavitha and Bhavitha Choorna of the whole plant of Centella asiatica Linn. Urban - Narang, Priyanka; Ansary, P Y; Oommen, Sara Monsy; Shincymol , V V (International Research Journal of Ayurveda & Yoga, 2023)
The drug Mandukaparni (Centella asiatica Linn. Urban) has been extensively used as medicine and also used for in homely preparations. In Ayurveda, Bhavana is a principal samskara (pharmaceutical procedure) being used to potentiate the drug and induce additional therapeutic properties in it. This process was carried out in the powdered whole plant (abhavitha choorna) of Mandukaparni (Centella asiatica Linn.Urban), by soaking it overnight into its own swarasa (fresh juice). The preliminary phytochemical evaluation of abhavitha choorna and bhavitha choorna (processed powder) of Mandukaparni (Centella asiatica Linn.Urban) was done and the water insoluble ash, tannin, extractive values and successive solvent extractive values were found more in bhavitha choorna when compared to abhavitha choorna of the drug, which revealed that the bhavana process can increase the potency and efficacy of the drug. The aim of present study is to compare the findings of phytochemical analysis of the both abhavitha and bhavitha choorna of the drug.